2017
DOI: 10.1002/jcb.26043
|View full text |Cite
|
Sign up to set email alerts
|

Runt‐Related Transcription Factor 2 (Runx2) Is Responsible for Galectin‐3 Overexpression in Human Thyroid Carcinoma

Abstract: Runx2 promotes metastatic ability of cancer cells by directly activating some of the mediators regarding malignancy. Galectin-3 (Gal-3) extensively expressed in normal and transformed cells and it is responsible for many cellular processes. In this study, we aimed to investigate whether there is any relationship between runx2 transcription factor and regulation of galectin-3 expression in different human thyroid carcinoma cell lines. To show effects of runx2 transcription factor on gal-3 expression, we develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Gal-3 is a member of the lectin family and plays an important role in cell–cell adhesion and cell–matrix interactions. Kaptan et al [ 102 ] revealed that regulation of Gal-3 expression was strongly correlated with Runx2 TF in human thyroid carcinoma; increase in Gal-3 gene expression was detected in patients with calcification [ 103 ].…”
Section: Cellular and Molecular Mechanisms For Calcification In Thmentioning
confidence: 99%
“…Gal-3 is a member of the lectin family and plays an important role in cell–cell adhesion and cell–matrix interactions. Kaptan et al [ 102 ] revealed that regulation of Gal-3 expression was strongly correlated with Runx2 TF in human thyroid carcinoma; increase in Gal-3 gene expression was detected in patients with calcification [ 103 ].…”
Section: Cellular and Molecular Mechanisms For Calcification In Thmentioning
confidence: 99%
“…RUNX2, also known as core binding factor α1 (CBFα1), is the most specific marker gene in the early stages of bone formation, and plays a key role in the regulation of cell proliferation in osteoblasts and endothelial cells [ 27 ]. Similarly, several studies have shown that RUNX2 is also closely associated with the occurrence and development of tumors, such as breast cancer [ 28 ], colorectal cancer [ 29 ], thyroid cancer [ 30 ], and pancreatic cancer [ 31 ]. RUNX3 has been defined as both a tumor suppressor and a tumor promoter, and it can play such contradictory roles even in the same tumor, which may reflect the complex role of RUNX3 in tumorigenesis [ 32 ].…”
Section: Introductionmentioning
confidence: 99%